Intra-articular Injection of Mesenchymal Stem Cells for the Treatment of Osteoarthritis of the Knee: A 2-Year Follow-up Study. (October 2017) - Jo, Chris Hyunchul; Chai, Jee Won; Jeong, Eui Cheol; Oh, Sohee; Shin, Ji Sun; Shim, Hackjoon; Yoon, Kang Sup
Background: The intra-articular injection of mesenchymal stem cells (MSCs) into the knee has shown a potential for the treatment of generalized cartilage loss in osteoarthritis (OA). However, there have been few midterm reports with clinical and structural outcomes. Purpose: To assess the midterm safety and efficacy of an intra-articular injection of autologous adipose tissue–derived (AD) MSCs for knee OA at 2-year follow-up. Study Design: Cohort study; Level of evidence, 3. Methods: Eighteen patients with OA of the knee were enrolled (3 male, 15 female; mean age, 61.8 ± 6.6 years [range, 52-72 years]). Patients in the low-, medium-, and high-dose groups received an intra-articular injection of 1.0 × 10 7, 5.0 × 10 7, and 1.0 × 10 8 AD MSCs into the knee, respectively. Clinical and structural evaluations were performed with widely used methodologies including the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and measurements of the size and depth of the cartilage defect, signal intensity of regenerated cartilage, and cartilage volume using magnetic resonance imaging (MRI). Results: There were no treatment-related adverse events during the 2-year period. An intra-articular injection of autologous AD MSCs improved knee function, as measured with the WOMAC, Knee Society clinical rating system (KSS), and Knee injury and Osteoarthritis Outcome Score (KOOS), and reduced knee pain, as measured with the visual analog scale (VAS), for up to 2 years regardless of the cell dosage. However, statistical significance was found mainly in the high-dose group. Clinical outcomes tended to deteriorate after 1 year in the low- and medium-dose groups, whereas those in the high-dose group plateaued until 2 years. The structural outcomes evaluated with MRI also showed similar trends. Conclusion: This study identified the safety and efficacy of an intra-articular injection of AD MSCs into the OA knee over 2 years, encouraging a larger randomized clinical trial. However, this study also showed potential concerns about the durability of clinical and structural outcomes, suggesting the need for further studies. Clinical Trial Registration: NCT01300598